Design of Micro Wind Power Plant using Dual Savonius Turbines - Saputra, Riza Hadi; Risna, Risna; Oktafiani, Fitri; Sampurno, Yusuf Cahyo; Ardito, Jheskia (Telkom University, 2024)
Wind power plants are one of the renewable energy solutions that are environmentally friendly and sustainable. The success of such plants heavily depends on the location, which plays a crucial role in determining the availability of wind. In addition to highlands, coastal areas can serve as suitable locations. Balikpapan, with its expansive coastlines, holds significant potential for harnessing wind energy as a source of electricity. However, the utilization of this wind energy, particularly on a micro-scale, remains suboptimal. Research conducted over three days recorded wind speeds between 4 m/s and 5 m/s, generating voltages between 3 volts and 4 volts, which is only 1/3 of the total potential voltage. There is still an untapped potential of about 2/3 or 6 volts that could be harnessed if wind speeds reach 12 m/s to 15 m/s. The study concludes that the wind speed at Airport Beach is not yet sufficient to produce the maximum possible voltage. The current wind speeds are only capable of powering a 5-volt capacity light, with the generated energy stored in a battery for later use.